Analisis Pemasaran Ikan Air Tawar Di Kecamatan Barong Tongkok Kabupaten Kutai Barat - Rizal, Samuel; Purnamasari, Elly; Susilo, Heru (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The purpose of the study was to determine the costs, income, marketing margins, marketing channels and marketing efficiency of freshwater fish in Barong Tongkok District, West Kutai Regency. This research was conducted from July 2021 to June 2022. The sample determination was based on the Census method, namely by taking one population group as a whole with a total of 4 respondents, namely tilapia cultivators business owners, Snowball Sampling method with a total of 4 respondents. The main data (primary) was obtained from business owners by means of interviews using a questionnaire. Data were analyzed by quantitative analysis. The results of the analysis show that the average cost of all respondent cultivators is IDR.11,359,817/year, the average profit is IDR. 3,140,183/year. The applicable marketing channels are level 0 channels and level 1 channels. The resulting marketing margin is IDR. 6000. Freshwater fish marketing channel in Barong Tongkok District, West Kutai Regency has an efficiency value of 83% so it can be concluded that the applicable marketing channel is efficient because the efficiency value is more than 50%.